North Atlantic Drift Sediments Constrain Eocene Tidal Dissipation and the Evolution of the Earth‐Moon System. Issue 2 (9th February 2023) - De Vleeschouwer, David; Penman, Donald E.; D'haenens, Simon; Wu, Fei; Westerhold, Thomas; Vahlenkamp, Maximilian; Cappelli, Carlotta; Agnini, Claudia; Kordesch, Wendy E. C.; King, Daniel J.; van der Ploeg, Robin; Pälike, Heiko; et al.
Abstract: Cyclostratigraphy and astrochronology are now at the forefront of geologic timekeeping. While this technique heavily relies on the accuracy of astronomical calculations, solar system chaos limits how far back astronomical calculations can be performed with confidence. High‐resolution paleoclimate records with Milankovitch imprints now allow reversing the traditional cyclostratigraphic approach: Middle Eocene drift sediments from Newfoundland Ridge are well‐suited for this purpose, due to high sedimentation rates and distinct lithological cycles. Per contra, the stratigraphies of Integrated Ocean Drilling Program Sites U1408–U1410 are highly complex with several hiatuses. Here, we built a two‐site composite and constructed a conservative age‐depth model to provide a reliable chronology for this rhythmic, highly resolved (<1 kyr) sedimentary archive. Astronomical components (g‐terms and precession constant) are extracted from proxy time‐series using two different techniques, producing consistent results. We find astronomical frequencies up to 4% lower than reported in astronomical solution La04. This solution, however, was smoothed over 20‐Myr intervals, and our results therefore provide constraints on g‐term variability on shorter, million‐year timescales. We also report first evidence that the g 4 – g 3 "grand eccentricity cycle" may have had a 1.2‐Myr period around 41 Ma, contrary to its 2.4‐Myr periodicity today. Our median precession constant estimate (51.28 ± 0.56″/year) confirms earlier indicators of a relatively low rate of tidal dissipation in the Paleogene. Newfoundland Ridge drift sediments thus enable a reliable reconstruction of astronomical components at the limit of validity of current astronomical calculations, extracted from geologic data, providing a new target for the next generation of astronomical calculations. Plain Language Summary: The traditional cyclostratigraphic approach is to align and correlate a geologic depth‐series with an astronomical solution. However, the chaotic nature of the Solar System prevents astronomers from precisely calculating planetary motions beyond 40–50 million years ago. This in turn limits the options for geologists to use the resulting oscillations in Earth's climate system as a metronome for determining geologic time. In this study, we reversed the cyclostratigraphic approach and used the highly rhythmical sedimentary deposits from Newfoundland Ridge (North Atlantic) to back‐calculate planetary motions at ∼41 million years ago. The superior quality of the Newfoundland Ridge geoarchive originates from the combination of relatively high sedimentation rates (∼4 cm/kyr) and the time‐continuous character of our two‐site composite record between 39.5 and 42.8 million years ago. In this work, we had to first overcome considerable challenges in reconstructing the timing of sediment deposition, which we did with highly resolved geochemical measurements from two sites. We then were able to extract information on the Earth's planetary motion and on the Earth‐Moon interactions. These astronomical reconstructions based on geological data can now be used by astronomers to describe the evolution of the solar system further back in time than was previously possible. Key Points: A new precession‐based cyclostratigraphy for the middle Eocene intervals of IODP Sites U1408 and U1410 Variability in astronomical fundamental frequencies (g‐terms) on million‐year timescales is larger than previously assumed Our precession constant estimate for 41 Ma (51.28 ± 0.56″/year) confirms earlier indicators of slower tidal dissipation in the Paleogene